Reconstruction with Composite Cement-Autoclaved Autograft after a Near-Total Excision of the Humerus for Osteosarcoma: A Case Report - Pan, K.L.; Zolqarnain, A.; Ong, G.B. (Malaysian Orthopaedic Journal, 2009)
Osteosarcoma occurring in the humerus is often confined to the proximal part, in which case, reconstruction after excision is less daunting. When the tumour spreads down the medullary cavity distally, a total humeral replacement is often required. This is costly and beyond the means of the average patient in a developing country. An amputation is often the procedure of first resort. We report a 13-year-old boy with osteosarcoma originating from the left proximal humerus, with involvement of the marrow reaching down to the distal diaphyseal-metaphyseal junction, leaving only 6cm of the distal humerus intact after wide resection. Reconstruction of the defect was done with a composite cement-autoclaved autograft fixed to the remaining humerus with a plate. At 40 months of follow-up, the patient is well with normal function of the elbow, wrist and hand. Salvaging the limb despite near total involvement of the humerus by high grade osteosarcoma is possible using material available in the average orthopaedic operating room.